The Double of Fyodor Dostoyevsky and the Double of Nikolai Akhsharumov: the Problem of Literary Connections - Володина, Наталья (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2016)
The article is devoted to the historical, literary and intertextual connections between Dostoyevsky’s novella The Double and Nikolai Akhsharumov’s novella of the same title. The research indicates that the two writers’ texts are linked by the dominant of psychological analysis, the theme of duality and the topos of St. Petersburg. However, the protagonists themselves, their doubles and the relationships between them are diametrically opposite in the works of Dostoevsky and Akhsharumov. This demonstrates the complex laws of literary evolution, which encompass not only the influence of a predecessor, but also taking issue with him.